STRATEGI KETERAMPILAN GURU DALAM MEMBERIKAN MOTIVASI BELAJAR SISWA DI SMA NEGERI 2 LIMBOTO - Rahmatia Luawo; Roy Hasiru; Imam Prawiranegara Gani; Radia Hafid; Rierind Koniyo (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The low enthusiasm and active participation of students due to the dominance of rigid normative learning is the background of this research activity. These operational problems trigger acute boredom and weakening of students' self-confidence in responding to instructions in the subject of Economics. The main focus of this scientific study is to analyze in depth the level of effectiveness of teachers' teaching skills strategies in boosting the learning motivation of grade XII students at SMA Negeri 2 Limboto. The steps of this descriptive qualitative research are operated through snowball sampling of informants involving subject teachers and a number of students. The primary field data collection procedure is collected through participant observation techniques, semi-structured interviews, and documentation studies, which are then analyzed interactively including the stages of data reduction, data presentation, and drawing sociological conclusions. Qualitative findings reveal that the implementation of pedagogical skills through the creation of ice-breaking activities, providing verbal-nonverbal reinforcement, and the application of problem-based learning methods has proven to be very reliable in breaking the ice of interactions in the classroom. Providing constructive feedback and humanistic classroom management also significantly foster students' independence and intellectual responsibility. The main conclusion confirms that optimizing a variety of teaching skills successfully transforms classrooms into dynamic, communicative, and enjoyable learning ecosystems. Secondary education practitioners are recommended to consistently improve instructional innovation to maintain the intrinsic motivation of the younger generation in a comprehensive and sustainable manner. ABSTRAK Rendahnya antusiasme dan partisipasi aktif siswa akibat dominasi pembelajaran normatif yang kaku melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu kejenuhan akut serta melemahnya kepercayaan diri peserta didik dalam merespons instruksi pada mata pelajaran Ekonomi. Fokus utama kajian ilmiah ini adalah menganalisis secara mendalam tingkat efektivitas strategi keterampilan mengajar guru dalam mendongkrak motivasi belajar siswa kelas XII di SMA Negeri 2 Limboto. Langkah-langkah penelitian kualitatif deskriptif ini dioperasikan melalui penarikan informan secara snowball sampling yang melibatkan guru mata pelajaran dan sejumlah siswa. Prosedur pengumpulan data primer lapangan dihimpun lewat teknik observasi partisipan, wawancara semi-terstruktur, serta studi dokumentasi, yang selanjutnya dianalisis secara interaktif meliputi tahap reduksi, penyajian data, dan penarikan kesimpulan sosiologis. Temuan kualitatif menyingkap bahwa implementasi keterampilan pedagogik melalui penciptaan kegiatan ice breaking, pemberian reinforcement verbal-nonverbal, serta penerapan metode problem-based learning terbukti sangat andal memecah kebekuan interaksi di dalam kelas. Pemberian umpan balik yang konstruktif dan pengelolaan kelas yang humanis juga secara signifikan menumbuhkan kemandirian serta tanggung jawab intelektual siswa. Simpulan utama menegaskan bahwa optimalisasi variasi keterampilan mengajar sukses mentransformasikan ruang kelas belajar menjadi ekosistem yang dinamis, komunikatif, dan menyenangkan. Praktisi pendidikan tingkat menengah direkomendasikan secara konsisten meningkatkan inovasi instruksional guna memelihara motivasi intrinsik generasi muda secara menyeluruh dan berkelanjutan.